Peran dan Tantangan Penggunaan Media Pembelajaran dalam Pendidikan Dasar: Meningkatkan Efektivitas dan Minat Belajar Siswa (International Forum of Researchers and Lecturers, 2024)
Learning and teaching, two familiar words in the realm of education, are like two sides of the same coin, inseparable from one another. They form the main pillars guiding individuals toward the gates of knowledge and wisdom. Learning, akin to an adventurous journey, is a continuous process of self-transformation. The interaction between individuals and their environment acts like a map guiding their steps. Every experience, every interaction, is like a footprint etched in the soil, leading individuals towards positive, active, and directed behavioral changes. This transformation, much like the metamorphosis of a butterfly, does not happen overnight. It requires time, patience, and proper guidance, much like the mentorship of a wise teacher, to help individuals reach their full potential. Teaching, on the other hand, is a well-orchestrated symphony. Under the direction of the maestro, the educators, the teaching process is meticulously designed, implemented with dedication, and carefully evaluated.